Efficacy and Safety of Topical Tranexamic Acid Alone or in Combination with Either Fractional Carbon Dioxide Laser or Microneedling for the Treatment of Melasma - Safaa Mamdouh Kamal; Doaa Salah Hegab; Gamal Mohamed El Maghraby; Amal Ahmad El- Ashmawy (Mattioli1885, 2023)
Introduction: Tranexamic acid (TXA) is a promising treatment modality for melasma. Microneedling (MN) and fractional carbon dioxide (CO2) laser were reported to enhance TXA transepidermal delivery. Objectives: To compare efficacy and safety of topical TXA alone or in combination with either fractional CO2 laser or MN for treatment of melasma. Methods: Thirty females with facial melasma were divided randomly into 3 equal groups after excluding pregnant and lactating women and those using oral contraceptives or other hormonal therapy. Patients of group A were treated with fractional CO2 laser and those of group B were treated with MN (4 sessions, 3 weeks apart for both) with immediate topical application of TXA 5% solution after sessions and daily application of 5% TXA cream for both groups. Patients of group C were treated by topical daily application of TXA 5% cream. Evaluation was done by modified melasma area and severity index scores (mMASI), patient satisfaction and dermoscopy. Results: Statistically significant improvement of mMASI was reported in all studied groups with a significantly better improvement in patients of groups A and B than those of group C, meanwhile the difference between groups A and B was statistically insignificant. Conclusions: Topical TXA is a safe and fairly effective treatment modality for facial melasma. Combining TXA with either fractional CO2 laser or MN yielded significantly better improvement than when used alone. Fractional CO2 laser carries the risk of post-inflammatory hyperpigmentation in patients with skin types III and IV and requires meticulous patient selection.